Designing Interactive Systems Conference 2021 2021
DOI: 10.1145/3461778.3462121
|View full text |Cite
|
Sign up to set email alerts
|

One Byte at a Time: Insights about Meaningful Data for Sustainable Food Consumption Practices

Abstract: Data have played an extensive role in sustainable HCI research by informing the impacts of our behavior on the environment and helping us make better environmental choices. However, in the area of sustainable food consumption and sustainable HCI, there is little investigation on the roles of food data for the design of technology. This paper presents findings from a qualitative study of sustainable-conscious individuals' food data seeking experiences. Our results show the way in which the current food data is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…In the case of China, Liu et al (2023) claimed that China's food system emits about 2.4 gigatons of CO 2 e and approximately 50% of its emissions occur during the production stage. To reduce the pollution emissions level, it is essential for the economies to enhance carbon literacy (Lindrup et al, 2023). In the empirical estimations, Li et al (2022) indicated around 3.0 gigatons of CO 2 e, where transportation accounts for 19%, while global freight transportation contributes around 36% of food-miles emissions, approximately double that of the production emissions.…”
Section: Nexus Of Food Variables and Co 2 Ementioning
confidence: 99%
“…In the case of China, Liu et al (2023) claimed that China's food system emits about 2.4 gigatons of CO 2 e and approximately 50% of its emissions occur during the production stage. To reduce the pollution emissions level, it is essential for the economies to enhance carbon literacy (Lindrup et al, 2023). In the empirical estimations, Li et al (2022) indicated around 3.0 gigatons of CO 2 e, where transportation accounts for 19%, while global freight transportation contributes around 36% of food-miles emissions, approximately double that of the production emissions.…”
Section: Nexus Of Food Variables and Co 2 Ementioning
confidence: 99%
“…The largest percentage of papers were classified at this level. This set of 21 papers included considerations of disciplinary networks (papers 19,55) organizations in general (papers 28,58,78), specific types of organization (papers 41,43,47,54,64) and individual organizations (papers 17, 51).…”
Section: Research Levelsmentioning
confidence: 99%
“…I designed probes to address specific research questions. For instance, one of the questions that emerged at the beginning of the PhD project was how people evaluate the sustainability of food products based on available data (see [87] for more details). For this, a cultural probe was designed that allowed participants to place stickers on food products and write their evaluation criteria on a sheet, in order for them to reflect on their assumptions about sustainable food products (see figure 3.1).…”
Section: Probe-driven Research Through Designmentioning
confidence: 99%
“…Contextual interventions include field deployments and enactments (see [87,88,90]). For the field deployments, the participants were provided with the probe with minimal instructions on how to use it, in order to encourage reinterpretations of the probe.…”
Section: Interventionsmentioning
confidence: 99%
See 1 more Smart Citation